ANALYSIS OF THE PRINCIPLES OF INTERNATIONAL HUMANITARIAN LAW ON THE USE OF BIOLOGICAL WEAPONS - Adelia Muqomimatim Mustika Dewi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research aims to examine whether the use of biological weapons constitutes a violation of the fundamental principles of International Humanitarian Law (IHL), specifically the principles of distinction, proportionality, unnecessary suffering, and precaution. This study employs a normative juridical method by analyzing international legal instruments such as the Biological Weapons Convention (BWC), the Geneva Conventions and their Additional Protocols, as well as historical precedents and documented uses of biological agents in armed conflicts. The analysis is conducted through systematic and historical interpretation, connecting the evolution of biological weapons with the contemporary framework of IHL. The findings indicate that biological weapons inherently contradict the core principles of IHL due to their indiscriminate nature, uncontrollable spread, prolonged suffering, and large-scale impact on civilian populations. These characteristics render biological weapons incapable of distinguishing between legitimate military targets and civilians, resulting in unavoidable and disproportionate harm. Moreover, their pathogenic properties produce excessive suffering and create significant risks beyond the battlefield, thereby violating the principles of unnecessary suffering and precaution. Consequently, the use of biological weapons in any armed conflict qualifies as a serious breach of IHL and may constitute a war crime under international legal regimes.